The analyse of poland economy within the context of full membership to European Union - Şen, Kadirhan (My University, 2005)
The purpose of this thesis is to analyze the transformation of Poland economy on the road to full membership to the European Union. In the thesis, first, in order to understand the past conditions that Poland suffered, the basic properties and handicaps of centrally planned economic system is analyzed. The thesis also includes the development and outputs of the enlargement process regarding the Central and Eastern European countries. Then the first non-socialist Poland government's radical economic programme is examined. This programme aimed to adapt market-oriented reforms by dismantling the old centrally planning economy mechanisms. Poland is the first country bringing market oriented reforms in Eastern Europe. The thesis covers the detailed analyse of macroeconomic environment which reflects the effects of this economic programme. Parallel to economic programme, Poland opened its economy to the world by liberalising its foreign trade. In a short period, Poland reached an impressive foreign trade performance. Increased exports accelerated the economic growth of the country. Also attracting foreign investment and the privatization process were vital for Poland's economic transition path. European Union was a very important target for Poland on the road to democratization and marketization. Consequently, in order to achieve this, Poland showed an impressive performance but European Union's enlargement strategies was also very helpful.

Bu tezin yazılmasındaki amaç Avrupa Birliğine tam üyelik yolunda Polonya ekonomisinin yaşadığı değişimi incelemektir. Tezde, önce Polonya'nın geçmişte sıkıntı çektiği koşulları anlamak için merkezi planlı ekonomik sistemin özellikleri ve handikapları incelendi. Tez ayrıca Orta ve Doğu Avrupa ülkelerini kapsayan genişleme sürecinin gelişimini ve sonuçlarını içermektedir. Daha sonra Polonya'daki ilk sosyalist olmayan hükümetin uyguladığı radikal ekonomik program incelenmiştir. Programın amacı eski merkezi planlı ekonominin mekanizmalarını kaldırarak yerine pazar ekonomisi ile ilgili reformları adapte etmekti. Polonya Doğu Avrupa ülkeleri içerisinde pazar ekonomisi reformlarını uygulamaya başlayan ilk ülkedir. Tez, bu ekonomik programın etkilerini yansıtan detaylı bir makroekonomik analizi de kapsamaktadır. Ekonomik programa paralel olarak Polonya dış ticaretini serbestleştirerek ekonomisini dünyaya açtı. Kısa bir süre içerisinde Polonya etkileyici bir dış ticaret performansına ulaşmıştır. Artan ihracat ülkenin büyüme hızını da arttırmıştır. Ayrıca yabancı yatırımı çekme ve özelleştirme sürecide Polonya'nın ekonomik değişimi yolunda hayati önem taşımıştır. Avrupa Birliği, Polonya için demokratikleşme ve pazar ekonomisine geçiş yolunda çok önemli bir hedefti. Sonuç olarak, Polonya, bu hedefe ulaşmak için etkileyici bir performans göstermiştir ancak Avrupa Birliği'nin genişleme stratejileri de bu doğrultuda çok yardımcı olmuştur.
Keywords: Avrupa Birliği_Polonya; Polonya_Ekonomik Gelişim